3-Acylated tetramic and tetronic acids as natural metal binders: myth or reality?. Issue 4 (16th February 2016) - Zaghouani, Mehdi; Nay, Bastien
Abstract : Stable salts and chelates of 3-acylated tetramic and tetronic acids could be prevalent under natural and physiological conditions, suggesting their importance for biological activities. Abstract : Covering: up to 2015 3-Acylated tetramic and tetronic acids are characterized by a low p K a and are likely to be deprotonated under physiological conditions. In addition, their structure makes them excellent chelators of metallic cations. We will discuss the significance of these chemical properties with regard to the biological properties and mechanisms of action of these compounds, highlighting the importance of considering them as salts or chelates for biological purposes, rather than acids.